Komunitas Semut (Hymenoptera : Formicidae) Pada Tanaman Padi, Jagung Dan Bawang Merah - A, Abtar (AGROTEKBIS, 2013)
The research aimed to know the community of ant (Hymenoptera : formicidae) on three different plants, namely paddy, corn and red onion. The research which took place in Sidera village Biromaru region of Sigi regency. A description method by using a purposive sampling technique was used to collect samples. The samples were obtained from fifteen baited-traps which were located in three station. There were five baited-traps in each station. The population of this research was all kind of formicidae (ant) in site experiment while all of those trapped ants were assumed as samples. Results of this research showed that there were in Sidera village Biromaru region of Sigi regency five Spesies of Formicidae found in observed plants. There were Solenopsis geminata, Anoplolepis gracilipes, Tetramorium sp, Pratrechium sp and Dolichoderus thoracicus